A Comparative Dictionary of Tagalog - Alter, Franz Carl (The Archive; Vol 4 (1981): Publication Four: A Comparative Dictionary of Tagalog, 2025)
The reason for the present article on the Tagalog language is this. Mr. Fabera, a private tutor of the young Count Wrbna showed me in April 1799 in the Imperial Court Library a Spanish-Tagalog dictionary in manuscript form; it is in quarto and two inches thick. In this manuscript are entered at the end Adverbios de lengua Tagala on 5 pages. He asked me what the Tagalog language was. I could not answer his question at once and admitted that I did not know it and had never read or heard anything about it. After that time I found by chance Tagalog also mentioned in P. Sim. Pallas comparative dictionary of 200 languages spoken in Europe and Asia, published in St. Petersburg in 1787 and 1789, in quarto, and I also read in Joh. Chrph. Gatterer’s Outline of Diplomacy, Gottingen 1789, large 8o, p. 41, Tagalog writing: popular writing in the Philippine Islands . Mr. Fabrera had the kindness to lend me in February 1800 for a short time his Spanish-Tagalog dictionary which is the property of the library of Count Wrbna, and I have compared the Tagalog words which Pallas quotes with the words of other Asian languages, for example those of Malay, Magindanao, Pampango, and so on.